2016
DOI: 10.1039/c6fo00466k
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis, structural characterization and antioxidant capacity assessment of a new lipophilic malvidin-3-glucoside–oleic acid conjugate

Abstract: The chemical modification of anthocyanins (water-soluble pigments) into more lipophilic compounds is very important to expand their application in the food, medical and cosmetic industries. In this work, the synthesis of a pure malvidin-3-glucoside-oleic acid ester derivative was achieved by enzymatic catalysis. This approach allowed us to synthesize a novel compound, malvidin-3-O-(6''-oleoyl)glucoside (Mv3glc-OA), which was structurally characterized by mass spectrometry and for the first time by NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 33 publications
7
54
0
Order By: Relevance
“…As shown in two acylated glucosides. 13 C NMR spectra confirmed that acylation took place at the primary hydroxyl group of glucose because of the C6'' signal downfield to 63.5 ppm, as already reported for analogous compounds (Cruz et al, 2016). Using NMR, it was determined that the ratio between Cy3glc-C8 and Dp3glc-C8 is 3:1, which is interesting considering the relative ratio of Cy3glc and Dp3glc in the extract, is approximately 0.5:1.…”
Section: Enzymatic Esterificationsupporting
confidence: 77%
See 1 more Smart Citation
“…As shown in two acylated glucosides. 13 C NMR spectra confirmed that acylation took place at the primary hydroxyl group of glucose because of the C6'' signal downfield to 63.5 ppm, as already reported for analogous compounds (Cruz et al, 2016). Using NMR, it was determined that the ratio between Cy3glc-C8 and Dp3glc-C8 is 3:1, which is interesting considering the relative ratio of Cy3glc and Dp3glc in the extract, is approximately 0.5:1.…”
Section: Enzymatic Esterificationsupporting
confidence: 77%
“…Previous work has reported the chemical acylation of a pure malvidin-3-O-glucoside Mv3glcto yield the stearic acid derivative, using stearoyl chloride in anhydrous acetonitrile (Cruz et al, 2015); however, the reaction was not regioselective and a complex mixture of mono-, di-, and tri-ester derivatives was obtained. In contrast, the regioselective synthesis of a pure malvidin-3-glucoside-oleic acid ester derivative was achieved by enzymatic catalysis with CalB, yielding only one ester product (21% conversion) (Cruz et al, 2016). The more lipophilic derivative did not show any reduction in antioxidant potential and protected more effectively a lipidic substrate from oxidation.…”
Section: Introductionmentioning
confidence: 99%
“… successfully acylated malvidin‐3‐glucoside with stearoyl chloride to provide the stearic acid derivative, but the reaction was not regioselective and mono‐, di‐ and tri‐ester derivatives were isolated that were very difficult to separate. In contrast, the research group showed that regioselective synthesis (where only the primary –OH on the glucose moiety was derivatised) of a malvidin‐3‐glucoside‐oleic acid ester derivative was achieved by enzymatic catalysis with Candida antarctica Lipase B ( Ca lB), giving only one ester product ; the derivative was more lipophilic and more stable to oxidation.…”
Section: The Futurementioning
confidence: 99%
“…[13] Other strategies for color stabilization of anthocyanins found in plants is to make acylated derivatives, which are usually used as food colorants because of their superior stabilityo vern on-acylated anthocyanins. [14,15,32,54] Supramolecular host-guest interactions have been widely applied in chemicala nd biochemical fields. Host-guest systems are formed by molecular recognition of ar eceptor (host) and a ligand (guest) by means of noncovalent interactions, such as electrostatic, hydrogen bonds, hydrophobic interactions,chemical coordination, van der Waals forces, and p-p stacking.…”
Section: Introductionmentioning
confidence: 99%